(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
The present text consists of the dramaturgy of O Pe®dido, a play by Beira Serra Circus and Theater Company, written by Fernando Vasques and Mimi Tortorella. There is also an introductory text that aims to briefly present the group, the piece and its creation process. O Pe®dido is the result of a rich collaborative process, where dramaturgy and staging were created concomitantly, from a theoretical-practical investigation on the Brazilian circus-theater.